2023
DOI: 10.3389/fchem.2023.1034473
|View full text |Cite|
|
Sign up to set email alerts
|

Additive manufacturing of Al2O3 ceramics with MgO/SiC contents by laser powder bed fusion process

Abstract: Laser powder bed fusion is a laser-based additive manufacturing technique that uses a high-energy laser beam to interact directly with powder feedstock. LPBF of oxide ceramics is highly desirable for aerospace, biomedical and high-tech industries. However, the LPBF of ceramics remains a challenging area to address. In this work, a new slurry-based approach for LPBF of ceramic was studied, which has some significant advantages compared to indirect selective laser sintering of ceramic powders. LPBF of Al2O3 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…However, it is crucial to note that exceeding the optimal amount of carbide additives can be counterproductive. As Ur Rehman et al [163,195] observed, excessive carbide additions would intensify their chemical reactions with ceramic oxides, generating gaseous byproducts like CO and SiO. This paradoxically increased porosity instead of reducing it.…”
Section: Pores Suppression Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is crucial to note that exceeding the optimal amount of carbide additives can be counterproductive. As Ur Rehman et al [163,195] observed, excessive carbide additions would intensify their chemical reactions with ceramic oxides, generating gaseous byproducts like CO and SiO. This paradoxically increased porosity instead of reducing it.…”
Section: Pores Suppression Methodsmentioning
confidence: 99%
“…In L-PBF, researchers have explored using ceramic slurries as an alternative feedstock to the conventional solid powder, offering several advantages [28,118,[161][162][163][164]. For example, Gahler et al [118] and Tian et al [28] formulated slurries by combining ceramic micro-powders, deionized water, and The feedstock preparation techniques for ceramic oxides in dAM: (a) gas atomization process [24]; (b) spray drying process [25]; (c) slurry deposition process using doctor blade [28]; (d) slurry deposition process using airbrush spray gun [161].…”
Section: Feedstock Preparationmentioning
confidence: 99%
“…This makes it an ideal choice for industries that require rapid prototyping as well as the production of highly precise and intricate parts, such as aerospace, medical, and automotive industries. Additionally, LPBF offers exceptional material utilisation, as it minimises waste and allows for the use of metal and its alloys, polymers, and even ceramics [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Layers are added to create the material component [2]. Sheet lamination, binder jetting, directed energy deposition, and selective laser milling are the most popular AM processes [3][4][5]. Around 1988, Crump [6] registered a patent on the three-dimensional printing (3DP) fused filament fabrication (FFF) method, and the schematic of the FFF 3D Printer is depicted in Figure 1.…”
Section: Introductionmentioning
confidence: 99%